Targeting ADAM10 in Cancer and Autoimmunity - Smith, Timothy M.; Tharakan, Anuj; Martin, Rebecca K. (Frontiers in Immunology, 2020)
Generating inhibitors for A Disintegrin And Metalloproteinase 10 (ADAM10), a zinc-dependent protease, was heavily invested in by the pharmaceutical industry starting over twenty years ago. There has been much enthusiasm in basic research for these inhibitors, with a multitude of studies generating significant data, yet the clinical trials have not replicated the same results. ADAM10 is ubiquitously expressed and cleaves many important substrates such as Notch, PD-L1, EGFR/HER ligands, ICOS-L, TACI, and the “stress related molecules” MIC-A, MIC-B and ULBPs. This review goes through the most recent pre-clinical data with inhibitors as well as clinical data supporting the use of ADAM10 inhibitor use in cancer and autoimmunity. It additionally addresses how ADAM10 inhibitor therapy can be improved and if inhibitor therapy can be paired with other drug treatments to maximize effectiveness in various disease states. Finally, it examines the ADAM10 substrates that are important to each disease state and if any of these substrates or ADAM10 itself is a potential biomarker for disease.